Kinetically Controlled Sequential Growth of Surface‐Grafted Chiral Supramolecular Copolymers. Issue 25 (17th March 2016) - Frisch, Hendrik; Fritz, Eva‐Corinna; Stricker, Friedrich; Schmüser, Lars; Spitzer, Daniel; Weidner, Tobias; Ravoo, Bart Jan; Besenius, Pol
Abstract: We report a facile strategy to grow supramolecular copolymers on Au surfaces by successively exposing a surface‐anchored monomer to solutions of oppositely charged peptide comonomers. Charge regulation on the active chain end of the polymer sufficiently slows down the kinetics of the self‐assembly process to produce kinetically trapped copolymers at near‐neutral pH. We thereby achieve architectural control at three levels: The β‐sheet sequences direct the polymerization away from the surface, the height of the supramolecular copolymer brushes is well‐controlled by the stepwise nature of the alternating copolymer growth, and 2D spatial resolution is realized by using micropatterned initiating monomers. The programmable nature of the resulting architectures renders this concept attractive for the development of customized biomaterials or chiral interfaces for optoelectronics and sensor applications. Abstract : A modular strategy for the kinetically controlled supramolecular polymerization of oppositely charged comonomers on gold surfaces enables architectural control at three levels: The β‐sheet sequences direct the polymerization away from the surface, the height of the non‐covalent polymer brushes is controlled by the stepwise nature of the alternating copolymer growth, and 2D spatial resolution is achieved by using micropatterned initiating monomers.